Hypoglycemic activity of Thai medicinal plants selected from the Thai/Lanna Medicinal Recipe Database MANOSROI II - Jiradej Manosroi (2018)
Ethnopharmacological relevance: Five medicinal plants including Anogeissus acuminata (Roxb. ex DC.) Gills. & Perr. (Combretaceae), Catunaregam tormentosa (Bl. ex DC.) Tirveng (Rubiaceae), Dioecrescis erythroclada (Kurz) Tirveng. (Rubiaceae), Mimosa pudica Linn. var. hispida Bren. (Fabaceae), and Rauwolfia serpentina (L). Benth. ex Kurz. (Apocyanaceae), which have been traditionally used for the treatment of diabetes mellitus and other diseases for several generations by the Thai-Lanna people in the Northern part of Thailand were investigated for their hypoglycemic activity in normoglycemic and alloxan, induced diabetic mice. Materials and methods: The aqueous extracts of the selected five medicinal plants were tested for their phytochemicals, free radical scavenging activity and hypoglycemic activity on 18 h fasted normoglycemic and alloxan induced diabetic mice over a period of 4 h comparing with the standard anti-diabetic drugs (insulin and glibenclamide) using two way analysis of variance (ANOVA) as analytical tool. Phytochemical analysis was performed using the standard methods while 2,2-diphenyl-1-picrylhydrazine (DPPH) was used to test for free radical scavenging activities of the medicinal plant extracts. Results: Phytochemicals detected in the extracts were glycosides, xanthones, tannins, alkaloids and saponins. Anogeissus acuminata showed the highest free radical scavenging activity with the IC50value of 11.00 μg/mL which was 4 folds of the standard ascorbic acid. Significant reduction in fasting blood glucose (FBG) levels of the normoglycemic mice was observed at 4 and 3 h with the extracts of Mimosa pudica (200 mg/kg bw) and Rauwolfia serpentina (100 mg/kg bw), and percentage decreases of 46.15 and 27.94% which were 0.76 and 1.47; 0.53 and 0.91 folds of insulin and glibenclamide, respectively. In alloxan induced diabetic mice, all extracts showed significant (p < 0.05) hypoglycemic activity, with the maximum FBG reduction of 78.96 at 100 mg/kg bw shown by Anogeissus acuminata at the 4 h. The hypoglycemic activity of Anogeissus acuminata was comparable to insulin (1.1 fold), but more potent than glibenclamide (1.76 folds). Conclusions: Medicinal plants selected from the Thai/Lanna Medicinal Plant Recipe Database MANOSROI II showed hypoglycemic activity in normoglycemic and alloxan induced diabetic mice. This study confirmed the traditional use of these medicinal plants for the treatment of diabetes mellitus and the thiazolidiendiones mimic hypoglycemic effects of the medicinal plants was suggested. © 2011 Elsevier Ireland Ltd.